2002
DOI: 10.1634/theoncologist.7-3-217
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Promise in the Treatment of Indolent Lymphomas

Abstract: In the era of conventional alkylating agent-based chemotherapy, advanced stage indolent lymphoma has been considered incurable. The failure of our traditional therapies to cure these patients, coupled with the indolent course of the disease and the elderly population affected, has fostered a nihilistic attitude about the treatment of these diseases. Twenty years ago, in the absence of interesting alternatives to alkylating agents, judicious use and reuse of alkylators was perhaps the best we could do. There ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Cyclophosphamide, the most frequently used alkylating agent in the treatment of lymphomas, was first described as therapy for diffuse large-cell lymphoma in 1975 [29].The CHOP regimen subsequently became standard treatment for patients with aggressive lymphomas and is also frequently used by clinicians to treat indolent lymphomas [5]. However, the standard CHOP regimen has not been proven to be capable of eradicating MRD in patients with follicular lymphomas, as documented by the persistence of cells bearing the bcl-2 gene rearrangement in blood and marrow.…”
Section: Cyclophosphamidementioning
confidence: 99%
See 2 more Smart Citations
“…Cyclophosphamide, the most frequently used alkylating agent in the treatment of lymphomas, was first described as therapy for diffuse large-cell lymphoma in 1975 [29].The CHOP regimen subsequently became standard treatment for patients with aggressive lymphomas and is also frequently used by clinicians to treat indolent lymphomas [5]. However, the standard CHOP regimen has not been proven to be capable of eradicating MRD in patients with follicular lymphomas, as documented by the persistence of cells bearing the bcl-2 gene rearrangement in blood and marrow.…”
Section: Cyclophosphamidementioning
confidence: 99%
“…Besides its activity as a single agent in the treatment of patients with follicular lymphomas, investigators have reported responses with mitoxantrone in combination with fludarabine, with or without dexamethasone, that appear better than those obtained with single-agent fludarabine in similar patient populations [5,23]. Four clinical trials using combinations of mitoxantrone and fludarabine (FM) were reported recently (Table 2).…”
Section: Mitoxantrone-containing Combination Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, this disease is characterised by a slow clinical pace and by responsiveness to a variety of treatment approaches [2]. Although the initial treatment results are satisfactory (remission rates up to 85%), relapse after standard chemotherapy [3][4][5][6][7][8][9][10] is almost inevitable and therefore these lymphomas are virtually incurable with conventional treatment approaches [2]. New approaches with stem cell transplantation [11][12][13][14], monoclonal antibodies [15][16][17] or cancer vaccines [18,19] are currently under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…20 In parallel, the introduction of targeted immunotherapy has revolutionized the management of patients with B-cell lymphomas. 21 These advances have two consequences. The first is that treated patients live longer and reach an older age where the surveillance of their disease becomes complicated by the morphological and perhaps immunophenotypic alterations related to age.…”
mentioning
confidence: 99%